Crawling exercises and hyperactivity among children with attention deficit-hyperactivity disorder - Bardos, Jane Alexis Lim Dy (2005)
Crawling exercises are very promising in helping children with ADHD optimize their learning potential. This study explored the effectiveness of crawling exercises on children with ADHD by comparing a control group with an experimental group based on the ADHD Checklist Scale, the ADHD Expected Bahavioral Frequency Chart, and the pretest-posttest scores of the two groups. It was found that crawling exercises when done intensively can minimize hyperactivity among special children but is not enough to sustain the decrease in hyperactivity. A follow up set of exercises for the matured STNR is imperative. Even without crawling exercises, hyperactivity can still decrease shortly if there is a set of routine and familiarity of tasks that children can follow in school.